G22(P) The evaluation of an innovative family-centred respiratory syncytial virus prevention programme to prevent bronchiolitis in vulnerable infants. (May 2019) - Cameron, D
Abstract : Aims: Respiratory syncytial virus (RSV) is a leading cause of bronchiolitis. Susceptibility is highest in infants born before 29+0 weeks gestation and those with congenital cardiac, pulmonary and immune anomalies. The American Academy of Paediatrics recommends five monthly prophylactic vaccinations within the first year of life for high-risk infants. Traditionally, eligible patients would attend monthly on three 'RSV' days. To produce a cost-effective service and to accommodate an increasing patient population, a flexible clinic was trialled in 2017. Attendance rates, the number of children hospitalised with RSV bronchiolitis and parental feedback were evaluated. Methods: Badgernet, neonatal clinic databases and email alerts were used to identify high-risk infants eligible for vaccination. A dedicated 'RSV Nurse' was tasked with appointing patients, ordering and administering vaccines and monitoring attendance. Review of Clinical Portal identified cases of hospitalisation with RSV bronchiolitis. Parental feedback was requested after the 2017 season. Results: Retrospective analysis showed the 2017 RSV season lasted 134 days with a total of 80 vaccination days compared to 15 previously. After excluding four deceased patients, 115 infants were eligible for vaccination. 80 patients – 70% of the cohort – were vaccinated in the RSV clinic. 70% of RSV clinic attendees received five RSV vaccinations. 30% of eligible patients were vaccinated in alternative locations elsewhere and were not included in analysis. Parental feedback showed 96% of parents would recommend the RSV prevention service with a return rate of 21%. Three cases of RSV bronchiolitis required hospitalisation. Conclusion: To provide continuity a dedicated nursing team allowed seamless delivery of care separate from the daily duties of the day care ward allowing flexibility. A significant increase in the number of vaccination days resulted in improved attendance to the clinic with 70% receiving the gold-standard five vaccinations. Hospitalisation, clinical requirement, parental choice and transfer of care to alternative units explained why 30% attending the clinic received fewer than five vaccinations. Nevertheless, 98% of clinic attendees avoided RSV bronchiolitis hospitalisation, which is exceptional. Despite positive feedback, a low return rate is recognised. We plan to request feedback mid-season next year to ensure we continue to adapt this high quality prevention programme and that return rate increases.